Pengaruh Karakteristik Chief Financial Officer (CFO) terhadap Akuntansi Prudensial - Zahrah, Shafa Aprilia; Hasnawati, Hasnawati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to empirically test and analyze the influence of Chief Financial Officer (CFO) characteristics on prudential accounting in banking sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022 with a total of 43 companies. This research was conducted using quantitative methods and using multiple linear regression analysis. The sampling determination technique in this study used purposive sampling. This research was formed because the role of the CFO is an important aspect in managing company finances, one of which is implementing prudential accounting. Prudential accounting is a principle used when making financial reports proactively to consider the possibility of uncertainty in business operations and is useful for anticipating uncertain things that will happen in business activities. Therefore, from the characteristics of this CFO to determine whether the CFO has applied this prudential principle when reporting financial statements. The results of the hypothesis testing in this study indicate that CFO Tenure has no effect on prudential accounting. CFO Education has an effect on prudential accounting. CFO Industry Experience has an effect on prudential accounting. CFO Performance has an effect on prudential accounting.